Displaying the Periphery: The Upper-Hungarian Museum and the Politics of Regional Museums in the Austro-Hungarian Monarchy. (2nd October 2019) - Veszprémi, Nóra
Abstract : The Upper-Hungarian Museum of Kassa/Kaschau/Košice was established in 1872 as one of the many ambitious but severely underfunded regional museums coming into being in the Austro-Hungarian Monarchy. This article examines how the museum negotiated the delicate balance between maintaining good relations with the capital, necessary for the sake of survival, and following its own local agenda. It discusses the history of the institution in the context of the complex political and administrative structure of Austria-Hungary, as an example of the dynamics between the Monarchy's "centers" and "peripheries." After 1867, Hungary's governments took the course of centralization, curtailing the political agency of the counties, while increasingly forcing non-Hungarian speakers in multi-ethnic regions such as Upper Hungary to adopt the Hungarian language. The article examines the museum's place in these processes, arguing that, rather than simply disseminating the narratives of the center, the museum conceptualized its own role in a more autonomous and multi-faceted way. Finally, it seeks to use the museum as an example of the "periphery" as an autonomous entity, and to question the usefulness of a simple binary of center and periphery in researching Austro-Hungarian culture.